Dinamika Hukum Dan Kontroversi Terkait Pengecualian Aborsi Di Indonesia - Rio Saputra; Didit Darmawan; Lina Wahyu Indayanti; Indah Wati Dwi Rini; Titik Ustiani (STIKes Ibnu Sina Ajibarang, 2023)
Abortion is a complex issue involving moral, legal and health considerations. Legal exceptions to abortion are a key focus in unraveling the dynamics of this complexity. Legal views and norms regarding abortion have undergone significant changes, reflecting social changes and understandings of women's reproductive rights. This study aims to analyze the regulations and legal views that define legal exceptions to abortion in Indonesia and how they relate to mitigating women's health risks. The research method involved a literature review and juridical analysis. The results show that the Health Law and Criminal Code provide exceptions for abortion under certain medical conditions, but the 40-day maximum time limit has been criticized. The role of certified health workers and constantly updated regulations play an important role. Implementation of legal exceptions remains challenging, especially in remote areas. In responding to this debate, regulations need to consider the humanitarian and psychological aspects of rape victims.